Metastatic Extramammary Paget’s Disease: Pathogenesis and Novel Therapeutic Approach - Fukuda, Keitaro; Funakoshi, Takeru (Frontiers in Oncology, 2018)
Extramammary Paget’s disease (EMPD) is a rare, slow-growing, cutaneous adenocarcinoma that usually originates in the anogenital area and axillae outside the mammary glands. EMPD mostly progresses slowly and is often diagnosed as carcinoma in situ; however, upon becoming invasive, it promptly and frequently metastasizes to regional lymph nodes, leading to subsequent distant metastasis. To date, several chemotherapy regimens have been used to treat metastatic EMPD; however, they present limited effect and patients with distant metastasis exhibit a poor prognosis. Recently, basic and translational investigative research has elucidated factors and molecular mechanisms underlying the promotion of metastasis, which can lead to targeted therapy-based emerging treatment strategies. Here, we aim to discuss current therapies and their limitations; advancements in illustrating mechanisms promoting invasion, migration, and proliferation of EMPD tumor cells; and future therapeutic approaches for metastatic EMPD that may enhance clinical outcomes.